554 Medicinal effects of microbubble bath on atopic eczema and psoriasis vulgaris (Balneo and PRM Research Journal, 2024)
The incidence of atopic eczema in the population reaches generally up to 25%. Skin diseases such as Atopic eczema and Psoriasis vulgaris are a worldwide problem. Use of topical corticosteroids is the first-line treatment for atopic dermatitis flare-ups. Last individual case studies led to the hypothesis: Baths with microbubbles in tap water can significantly support the treatment of skin diseases. Microbubbles penetrate deep into the skin pores. Micro implosions occur on the pore walls, which mechanically affect nerve endings and vascular microcapillaries. In addition, due to the implosion of microbubbles, the mechanical effect leads to an increased release and flushing of substances contained in the skin pores. A total of 30 patients were selected for the study, of which 15 were included in the Study Group and 15 in the Control Group. The effects were monitored on the objectively evaluable dermatological calculators PASI, EASI, SCORAD, and DLQI Score, Quality of life, and Number and condition of foci. The project responded to the hypothesis that microbubbles in the water phase, produced by special generators, in the size range of 1-100 µm, may in the future become a fundamental innovation in balneological treatment in the form of new treatment procedures.